Determinants of Language Attitudes of Elshinta Semarang Radio News Broadcasters and Radio Republik Indonesia (RRI) Pro 1 Semarang - Prasetiyo, Moh. Henri; Rokhman, Fathur; Zulaeha, Ida (Universitas Negeri Semarang, 2020)
The reality in the media world today is that apart from RRI and TVRI, private radio and television are also very concerning in their role as the coach of the Indonesian language. The purpose of this study was to analyze the factors that tend to influence the attitude of the news announcers Radio Elshinta Semarang and RRI Pro 1 Semarang. This research design uses descriptive qualitative. The data collection method used was the observation method. The data collection technique in this study was a record and note technique. The instrument in this study was the researcher himself. Data collection tools used were data collection guides and data cards. Miles and Huberman's data analysis model was used in this study. Based on the results of data analysis, internal factors that affect the language attitudes of news announcers Radio Elshinta Semarang and Radio Republik Indonesia (RRI) pro 1 Semarang are language mastery factors (cognitive component), other language mastery factors (language contact), preference factors (affective component) and language ideology factor (language belief). The results of this study provide theoretical and practical advantages. The benefits of this study can produce concepts regarding language attitudes in order to enhance sociolinguistic scientific treasures and help understanding sociolinguistic studies, especially in relation to language attitudes and can be a guide for news broadcasters to be able to be positive in speaking in public spaces.